Addressing Opportunities & Misunderstandings of ASCP International Certification in the Philippines. (28th October 2021) - Finnegan, K; Tanabe, P; Baker, J
Abstract: Introduction/Objective: The objective of this study is to identify the positive viewpoints and misunderstandings Filipino applicants have about the BOC's international credential and credential maintenance programs. With a total of 10, 836 MLS(ASCPi) certificants, the Philippines is the BOC's largest and most successful international certification market. However, despite the Philippines being the BOC's largest international certification market, the BOC only certifies about a third of eligible Filipino graduates each year. Therefore, to encourage additional interest in achieving BOC credentials and to eliminate misunderstanding surrounding the BOC's Credential Maintenance Program (CMP), the ASCP BOC International Credentialing Committee created and deployed a survey. The purpose of the survey was to learn as much as possible about the medical laboratory scientist certification market in the Philippines, as well as determine what opportunities Filipino's were afforded after they earned their credential. The resulting report based on analysis of the survey results showed there are a number of issues affecting Filipino participation in the BOC's credential and CMP offerings. Methods/Case Report: 422 individuals from 44 countries of education participated in the survey. This study is a summary of results from the 265 Filipino respondents. Results (if a Case Study enter NA): This study confirmed a number of assertions the BOC had about the Filipino credential market. The most important of these assertions is MLS(ASCPi) certification is appealing to Philippine- educated individuals due to its portability (i.e., work eligibility, emigration, etc.). Conclusion: The BOC should continue leaning into the portability of MLS(ASCPi) certification, but also needs to do a better job of promoting our other international certifications for which Filipinos may be eligible. The BOC needs to place greater emphasis on educating Filipinos on the importance of CMP and on what can be used for CE towards CMP. For example, the BOC needs to create an outreach campaign that helps Filipino credential holders understand CE earned for their PRC (i.e., Philippines-licensure requirements) can also be used for their CMP. Finally, considering the popularity of BOC certification in the Philippines, the BOC should work on creating more content that focuses on promoting the usefulness of pursing an advanced credential, the portability of certification, and the overall demystification of CMP.